Internalization of Quality Management Standards: A Literature Review. Issue 1 (2nd January 2020) - Tarí, Juan José; Molina-Azorín, Jose F.; Pereira-Moliner, Jorge; López-Gamero, María D.
Abstract: This work examines the literature on the internalization of quality management standards via database searches (Web of Science, Emerald, ScienceDirect, and ABI/Inform-ProQuest). This review describes the characteristics of the relevant literature (theoretical or empirical, countries of study, and methods used), the internalization process (two constructs to measure internalization and items under each construct), drivers (reasons for seeking certification, quality culture, leadership, and training), and the effects of internalization (customer, people, and social results). Engineering managers can consider these aspects and associated drivers when they seek to improve the current processes and performance of their firms. On the basis of this review, this article identifies gaps in the literature and proposes future research areas.